Digital tools and active leaning in an online university: Improving the academic performance of future teachers - Ingrid Mosquera Gende (OmniaScience, 2023)
Digital tools are part of any online educational context. When it comes to training future teachers, this point is crucial because they will transfer this technology to their classrooms. Additionally, incorporating these digital resources as part of an active learning proposal will contribute to future teachers' motivation, self-regulation, and autonomy and positively influence their academic performance. This piece of research refers to the evaluation of an educational active learning proposal in which a pre-experimental design without a control group was used in order to study the possible relationship between the use of digital tools and the academic performance of the students. A sample of 908 students participated, distributed in three academic years. Results show that those who used more tools as part of the active learning proposals obtained better final marks, as well as a higher grade in the continuous assessment activities, which they also completed in a higher percentage (p<0.001). It can be concluded that the use of digital tools within an active learning proposal contributes to an improvement in the academic performance of future teachers as well as in the participation and engagement of the students.